2013
DOI: 10.5171/2013.821692
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variations in Lumbricals of Hand – A Cadaveric Study

Abstract: The hand is a prehensile organ, it is endowed with grasping and precision movements for skilled work and it acts as a chief tactile apparatus. Thus human hand is a revolution in evolution. Indeed the lumbricals of the hand by producing flexion at the metacarpophalangeal joints and extension at the interphalangeal joints helps in writing, stitching and any other forms of precision work. A study was conducted in the department of Anatomy, Kasturba Medical College, Manipal with 30 cadavers of both sexes. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Similar finding was documented by Hosapatna M et al and Mutalik AM [Table 2]. [3,12] Among the variations of lumbricals studied, split insertion is the commonest variation reported. Split Insertion was commonly encountered in 3rd and 4th lumbricals.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Similar finding was documented by Hosapatna M et al and Mutalik AM [Table 2]. [3,12] Among the variations of lumbricals studied, split insertion is the commonest variation reported. Split Insertion was commonly encountered in 3rd and 4th lumbricals.…”
Section: Resultssupporting
confidence: 84%
“…Split insertion is an atavistic condition presenting as doubling of muscles as in lower animals (Virginian oppsum). [13] Hosapatna M (2013) [3] 30 1 (3.33%) Mutalik AM (2011) [12] 30 2 (6.67%) Present Study (2020) 74 2 (2.70%) [14] 107 -29 (27.1 %) 27 (25.2%) Mutalik AM(2011) [12] 30 8 (26.67%) -1 (3.3%) Hosapatna M (2013) [3] 30 1 (3.3%) --Parminder K (2013) [2] 50 - It was observed in our study that first lumbrical was found to be more bulky than other lumbricals in most of the specimens. However, clear hypertrophy was observed in only one specimen [Figure 9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This represents 5.1% of the total sample size which is somewhat closer to the percentages (3.3%) of that of the same variation reported by Mutalik [17]. A similar finding of 3.3% bipinate second lumbrical was reported from a couple of studies [18][19]. In contrast to this, another study reported quite a high percentage (45%) of second lumbrical bipinate nature [20].…”
Section: Lumbricalssupporting
confidence: 87%